'Offending doesn't happen in a vacuum': The backgrounds and experiences of children under the age of 14 years who offend. Issue 2 (June 2022) - Reil, Jerome; Lambie, Ian; Allen, Ruth
Relative to those who first offend in adolescence, younger children who offend are at increased risk of engaging in serious, persistent, and violent offending. In addition, these children are at risk of a range of adverse psychosocial outcomes across the lifespan. Early intervention with children at risk of offending is therefore critical to support children to thrive and reduce offending and victimisation rates. This study sought to explore the backgrounds and experiences of children who offend prior to the age of 14 years to shed light on the development of child offending and assist early intervention efforts. Interviews with family members (with lived experience of interacting with the child welfare and child offending system) and frontline child welfare and judicial professionals (who directly engage with children who offend) ( n = 33) were conducted. Their experiences show that children who offend have clear, significant, and unaddressed child welfare concerns, including growing up in poverty and experiencing abuse, which cumulatively impacts on children's normative development and can eventually culminate in offending. Participants called for urgent action to address the sociostructural concerns that underlie child welfare concerns and provide prompt and effective assistance to families in need to support children to thrive and prevent future victimisation.